2018
DOI: 10.1371/journal.pone.0196757
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison of three common essential oils mosquito repellents as inhibitors of the Ross River virus

Abstract: BackgroundThe essential oils of Cymbopogon citratus (CC), Pelargonium graveolens (PG) and Vetiveria zizanioides (VZ) are commonly used topically to prevent mosquito bites and thus the risk of infection by their vectored pathogens such as arboviruses. However, since mosquito bites are not fully prevented, the effect of these products on the level of viral infection remains unknown.ObjectivesTo evaluate in vitro the essentials oils from Reunion Island against one archetypal arbovirus, the Ross River virus (RRV),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Also, EOs may target genome related sites as revealed by genetic approaches [31]. Towards a certain type of virus, mechanisms of action may be EO dependent [32], possibly owing to the constitutional variations of the EOs. Summing up, the direct interaction of EOs with free viruses tends to be the most common mode of action.…”
Section: Other Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, EOs may target genome related sites as revealed by genetic approaches [31]. Towards a certain type of virus, mechanisms of action may be EO dependent [32], possibly owing to the constitutional variations of the EOs. Summing up, the direct interaction of EOs with free viruses tends to be the most common mode of action.…”
Section: Other Mechanisms Of Actionmentioning
confidence: 99%
“…Ralambondrainy et al [32] reported that monoterpene-rich Cymbopogon citratus and Pelargonium graveolens EOs exhibited higher antiviral effect on the Ross River Virus, while the sesquiterpene-rich Vetiveria zizanioides EO showed an insignificant effect. However, it seems arbitrary for the author to draw an inference that the antiviral competency was ascribed to the monoterpenes without further experimental proofs.…”
Section: Effect Of Polarity Of the Components On Anti-viral Activitiesmentioning
confidence: 99%
“…To further characterize the antiviral mechanism and the stage of ZIKV infection affected by D. apetalum extract, we examined the impact of the plant extract on various stages of the dissected virus replication cycle (pre-entry, entry and post-entry). In addition, wash steps were included to ensure the specificity of the treatment on the distinct stage examined [22,33]. In order to study pre-entry—more specifically, the ability of D. apetalum to induce host cell innate immunity prior virus addition [34]—A549 cells were pretreated with D. apetalum (200 µg·mL −1 ) for 6h (Figure 4A: pre-treatment).…”
Section: Resultsmentioning
confidence: 99%
“…Peppermint and lavender were effective as potential repellents in cotton with inclusion complexes of β -cyclodextrin [ 68 ]. Currently, eco-friendly and cost-effective EOs with antiviral capacity against arboviruses such as Ross River virus (RRV) are being studied [ 69 ]. Three EOs from Cymbopogon citratus (CC), Pelargonium graveolens (PG), and Vetiveria zizanioides (VZ) with repellent activities were evaluated for antiviral effects, in terms of prevention of viral entry, using a wild-type RRV-T48 strain, and viral replication, using a recombinant RRV expressing Ren luciferase.…”
Section: Current Technologies For the Development Of Effective Andmentioning
confidence: 99%